Genetic and biochemical analysis of ACE inhibitor-induced angioedema in black and coloured South Africans - Moholisa, Retsilisitsoe Raymond (Division of Medical Biochemistry, 2015)
Angiotensin converting enzyme inhibitors (ACEi) are routinely used as first line treatment for hypertensive patients because of their protective effects against heart and kidney disease. Despite their clinical benefits, ACEi used is associated with adverse side effects such as life threatening angioedema (ACEi-AE) and persistent dry cough (ACEi-cough)